The Determination of Freezing Effect for the Design of Grounding Grid via Logistic Mapping Genetic Algorithms for Power Transmission Substations - Gürsu, Barış; İnce, Melih Cevdet (Van Yüzüncü Yıl Üniversitesi, 2009)
Power transmission substations are the most important part of the interconnected system for the transfer of the electrical energy from the power plant to the consumption point , and for the the developing of different voltage levels. Before the construction of a substation, the first important and top priority operation is the design of the grounding grid. A grounding grid should be full operational during the iffetime of the power transmission system. Otherwise, unavoidable loşs of lives or financial loşs are arise. For this reason, this work deals with the freezing effect for the design of grounding grid, which is an important consideration factor. Initially, a secured designed grounding system Will be dangerous for the lives and power system because of (he freezing effect. This work discuss the effect of freezing for the system safety with the Logistic Mapped Genetic Algorithms (LHGA) method, systematically. The effect of freezing for the design of ground network is specicified by the programs Mitten in MATLAB both LHGA and Random Genetic Algorithms (RGA) . Then, on the one handı the effect of the frozen soil on the design of grounding network is determined, and on the other hand, (he performance of the LHGA on the design problem of the grounding grid with freezing effect.

İletim Merkezleri, elektrik enerjisinin üretildiği noktadan tüketildiği noktaya kadar iletim hatları vasıtasıyla taşınmasında, farklı gerilim seviyelerinin oluşmasında, enterkonekte sistem zincirinin en önemli halkasını oluşturmaktadır. İletim merkezi kurulmadan önce yapılması gereken en önemli ve en ilk işlemlerden biri de topraklama ağlarının tasarımıdır. Topraklama ağı, iletim merkezinin yıllarca faaliyetini sürdüreceği her anda, kendisinden beklenen görevlerini eksiksiz yerine getirmelidir. Aksi taktirde telafisi güç, can ve maddi kayıpların oluşması kaçınılmazdır. Bu nedenle, bu çalışmada, topraklama ağlarının tasarımında dikkat edilmesi gereken hususlar içerisinden, don olayının etkileri ortaya konulmuştur. Başlangıçta emniyeti sağlayacak şekilde dizayn edilen topraklama sistemi, sonradan don olayına bağlı olarak canlıların ve güç sisteminin güvenliği yönünden büyük tehlikeler arz edebilir. Bu çalışma, Lojistik Haritalı Genetik Algoritmalar (LHGA) metoduyla topraklama sisteminin emniyetinde don olayını sistematik olarak tartışır. Topraklama ağı tasarımında don olayının etkisi hem LHGA hem de Rassal Genetik Algoritmalara (RGA) dayalı Matlab' ta hazırlanan programlar ile belirlenmiştir. Böylece, bir yandan don tutmuş toprağın topraklama ağı tasarımındaki etkisi belirlenirken, diğer yandan LHGA I ın don etkili topraklama ağı tasarımı problemindeki performansı da izlenmiştir.
İletim Merkezlerinin Topraklama Ağlarının Tasarımında Lojistik Haritalı Genetik Algoritmalar Yardımıyla Don Etkisinin Belirlenmesi